Actividades turísticas recreativas y las oportunidades socioeconómicas en el cantón Montalvo - Meneses Martínez, Delia Verónica (2019)
This research project focuses on the study of recreational tourist activities as socioeconomic opportunities in the canton Montalvo. It undertakes a review of the literature that was relevant for the research that were: recreational tourism activities, economic impacts, natural resources among others. Each of the topics was expressed in detail, but limiting the information only to the direct relationship with the topic of study, so as to obtain a clear understanding of the issues involved and to be able to achieve the objectives that were set. It has applied a survey of 10 questions to certain sample of the population that visit the river Crystal that was one of the recreational tourist activities that the canton Montalvo has more economic impact